Papua, Pancasila & NKRI - Waterpauw, Paulus; Runturambi, Arthur Josias Simon; Tangkudung, Audrey G. (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Pancasila is the ideology of the Indonesian state, which allows us to integrate the diversity that exists in Indonesia into a unified Indonesian state. Five important values are included as guidelines for the state of Indonesia. The revival of the values of Pancasila for state administrators has many implications. Start with being tough and sensitive to the surrounding issues, includingnational issues. Second, of course, if the state administrators have Pancasila values, the interests of the Papuan people will take precedence over the interests of individuals or groups. Furthermore, discipline in carrying out obligation. Besides that, they able to control himself, including his own family. The method for collecting data from articles uses a literature review from several literatures such as: magazines, books and also articles. The gap is still visible, because the results of the study show that the activation of the Pancasila values carried out in Papua has not been fully implemented. The most important key forin revitalizing these values is the application of principles by three elements of state government: local government local (Pemda), DPR Papua (DPRP), as well as Papuan People's Parliament (MRP). Andhope that we all can absorb, apply, and operate values in Pancasila in life in a country Unitary Republic of Indonesia.